2020
DOI: 10.3906/tar-1912-76
|View full text |Cite
|
Sign up to set email alerts
|

Seed fatty acid compositions and chemotaxonomy of wild Crambe (Brassicaceae) taxa in Turkey

Abstract: Wild Crambe species have greater potential than Crambe hispanica in industry, medicine, and as a vegetable, etc. A total of 53 germplasm accessions, belonging to 7 taxa, were collected from Turkey's natural flora. The accessions consisted of C. orientalis var. orientalis (18 accessions), C. orientalis var. dasycarpa (1 accession), C. orientalis var. sulphurea (2 accessions), C. tataria var. aspera (3 accessions), C. tataria var. tataria (26 accessions), C. grandiflora (1 accession), C. orientalis var. sulphure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…They have a high content of bioactive compounds, such as flavonoids, phenolics, anthocyanins, phenolic acids, and non-nutritive and nutritive compounds such as essential oils, vitamins, minerals, etc. Recent research has shown that crude plant species have excellent medicinal value and healthcare functions, something which is also apparent from their familiar usage since ancient times for therapeutic, religious, cosmetic, nutritional, and beautification purposes [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…They have a high content of bioactive compounds, such as flavonoids, phenolics, anthocyanins, phenolic acids, and non-nutritive and nutritive compounds such as essential oils, vitamins, minerals, etc. Recent research has shown that crude plant species have excellent medicinal value and healthcare functions, something which is also apparent from their familiar usage since ancient times for therapeutic, religious, cosmetic, nutritional, and beautification purposes [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Plant species have increasing importance for people due to their use in the various spheres, such as pharmaceutical, food, and cosmetic industries, which draw attention to some potential plant species containing biologically active substances. In-depth knowledge of the composition and properties of the plants' anatomical parts, differences in the design of the biologically active profile relative to the area's geographical characteristics, methods of analysis, and others, are among the main areas of knowledge of their application [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Herbal plants are an important source of traditional medicine and play a key role in global health [ 1 , 2 , 3 , 4 , 5 ]. Turmeric ( Curcuma longa L.) belongs to the family Zingiberaceae , which includes rhizomatous herbaceous perennial herbs with heights of 60 to 90 cm; there are more than 40 commercially cultivated species of Curcuma longa [ 6 ].…”
Section: Introductionmentioning
confidence: 99%